What is the value of y in rhombus LMNO
A)4
B)6
C)12
D)24

- youngnephew34

What is the value of y in rhombus LMNO
A)4
B)6
C)12
D)24

- jamiebookeater

See more answers at brainly.com

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions

- youngnephew34

##### 1 Attachment

- phi

try to write an equation that shows the two halves of a diagonal are equal

- youngnephew34

|dw:1440159145510:dw|

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- youngnephew34

hold on

- youngnephew34

Y+12=6x

- phi

yes,
now write the other equation (for the other diagonal)

- youngnephew34

\[Y=3x\]

- phi

we have two equations and two unknowns (x and y are the unknowns)
do you know how to solve them?
Y+12=6x
y= 3x

- phi

one way is to use "substitution", the other way is "elimination"

- youngnephew34

For the Y+12=6x don't you suppose to subtract one side from another

- phi

in this problem, substitution works pretty well.
start with the equations:
y+12=6x
y= 3x
notice the 2nd equation says "y is the *same thing* as 3x"
we use that to replace the y in the first equation with 3x (erase the y and put in 3x instead)
can you do that?

- youngnephew34

you will substitute the 3x in to y right

- phi

what equation do you get ?

- phi

erase the y and put in 3x instead

- youngnephew34

so 3x+12=6x

- phi

yes. now we have just 1 unknown... that is good.
to solve I would start by adding -3x to both sides, like this
3x - 3x + 12 = 6x - 3x
now simplify

- phi

on the right side you have 6 x's take away 3 x's. how many x's do we have?

- youngnephew34

3x

- phi

ok, but write out the whole equation (so we don't get confused)
3x - 3x + 12 = 3x
on the right side, we have 3x's take away 3 x's

- phi

*left side

- youngnephew34

3x+12=3x

- phi

almost. 3x - 3x is not 3x

- youngnephew34

so really 12=3x

- phi

yes
last step. divide both sides by 3

- youngnephew34

x=4

- phi

the question asks for "y" not x
but from the equations we know
y= 3x
can you find y (knowing x is 4) ?

- youngnephew34

Y=4 srry bout that

- phi

no, you were correct the first time
x=4
but we can find y using
y= 3*x

- youngnephew34

so divide 4=3x

- phi

y= 3x
says y is the same thing as 3 times x
if we knew what x is (as a number) we would multiply it by 3 and we would get y (as a number)
but from the earlier steps you found x is 4
that means we can find y using that equation.
can you try?

- phi

in other words, in
y= 3*x
erase the x and put in 4 instead (because x is the same thing as 4)

- youngnephew34

Instead you would do 4x3 right

- phi

yes, but write it 4*3 (because using x for multiply is confusing... it might mean "x" the variable)

- youngnephew34

ok so 4*3=12

- phi

right,
y=3x
y=3*4
y=12
this problem took lots of steps. See if you can go over the steps, and try to understand the way we found y is 12.

- youngnephew34

so 3x+12+6x 3x-6x=3x 12/3=3/3
12/3=4
x=4
4x3=12

- phi

3x+12=6x
then add -3x to both sides
3x-3x + 12 = 6x-3x
simplify to get
0+12 = 3x
or
12=3x <-- notice we have 3x, not just 3)
4=x

- phi

then use
y=3x
when x is 4 then y = 3*4 =12

- youngnephew34

ok got it and one more to check

Looking for something else?

Not the answer you are looking for? Search for more explanations.